Use of potassium polyaspartate on white wines: Interaction with proteins and aroma compounds. (June 2023) - Natolino, A.; Tat, L.; Gallo, A.; Roman, T.; Celotti, E.
Graphical abstract: Highlights: Potassium polyaspartate (KPA) increased the wine protein stability indices. KPA significant decreased unstable wine protein content (up to 92%). Logistic model well described the KPA and storage temperature effect. PCA analysis didn't highlight significant effects on aroma content. A multifunctionality of KPA on wine stability and quality was highlighted. Abstract: The precipitation of tartaric salts represents one of the main visual sensory faults of white wines. It can be prevented by cold stabilization or adding some adjuvants, such as potassium polyaspartate (KPA). KPA is a biopolymer that can limit the precipitation of tartaric salts linking the potassium cation, however, it could interact also with other compounds affecting wine quality. The present work aims to study the effect of potassium polyaspartate on proteins and aroma compounds of two white wines, at different storage temperatures (4 °C and 16 °C). The KPA addition showed positive effects on the quality of wines, with a significant decrease of unstable proteins (up to 92%), also related to better wine protein stability indices. A Logistic function well described the effect of KPA and storage temperature on protein concentration (R 2  > 0.93; NRMSD: 1.54–3.82%). Moreover, the KPA addition allowed the preservation of the aroma concentration and no adversely effects were pointed out. Alternatively to common enological adjuvants, KPA could be considered a multifunctional product against tartaric and protein instability of white wines, avoiding adverse effects on their aroma profile.